Obaluaye - Badmus, Jide (FlowerSong Press, 2022)
The poems in this book talk of cradles and graves and every experience in-between, employing the duality attribute of the Orisha of epidemics. Each poem is an experience of health and death wrapped in a pod, of strength and flaws and a thirst for things that elude. This collection explores the human cycle-the routine of life and death (and a possibility of restoration, rebirth). It seeks to understand the things that haunt us-our fears, our nightmares, quest for freedom, the weight of responsibilities, the paradox of hope, devotion and betrayals, failed states and the covid-19 pandemic...
Keywords: Poetry